EVALUASI PELAYANAN TRANSPORTASI PUBLIK KORIDOR 2 KOTA SEMARANG (BANYUMANIK - JALAN PEMUDA) - YUSUF, AHMAD; NURQOIM WALINNAIM, MUHAMMAD; GALIH PAMUNGKAS, WARDANA; INTAN PRATIWI, YESINA (Civil Engineering of Universitas Islam Nahdlatul Ulama Jepara, 2023)
One type of public transportation designed to meet the mobility needs of the people of Semarang City is the Trans Semarang Bus. The level of service provided by the Trans Semarang Bus to customers and the level of service provided on weekends and weekdays will be the focus of this research. This research method employs a quantitative descriptive approach. The method of data collection is carried out by using a questionnaire. Stages of using quantitative analysis techniques to analyze data. Consumers who use the Trans Semarang Bus have a negative response (are not satisfied), according to the results of the Service Satisfaction Index (IKP). The majority of respondents gave a negative score (dissatisfied) to the difference in scores between performance and expectations, which shows this. The x2 count is obtained from the x2 table, from the chi-square analysis results. The value of 3.841 is the result of x2 d.b=1 when the x2 table used is α = 5%. Therefore, x2 count (2.007) table x2 (3.841), shows that Ho is accepted and Ha is rejected, indicating that the Trans Semarang Bus service on weekends and weekdays is the same.